Decoupling Between Extremely Closely Spaced Patch Antennas by Mode Cancellation Method - Sun, Libin; Li, Yue; Zhang, Zhijun (IEEE transactions on antennas and propagation, 2021)
In this article, an inductance-based decoupling scheme is proposed to reduce the mutual coupling between extremely closely spaced microstrip antennas. The original strong coupling can be effectively suppressed by simply inserting a lumped inductance in between. To offer a systemic design guideline for this decoupling strategy, a mode cancellation method, based on the synthesis of common mode (CM) and differential mode (DM), is proposed. The inserted inductance plays a role of tuning CM and DM impedances to a similar status, which has an equivalent decoupling effect according to the theory of microwave network. Alternatively, the lumped inductance could also be replaced by an inductive connecting strip for a concise topology. To validate the proposed decoupling concept, a prototype is simulated, fabricated, and measured. The experimental results show that the poor isolation of 5 dB is improved to better than 15.4 dB across the entire matched bandwidth of 2.394-2.530 GHz, with an extremely close edge-to-edge distance of 0.016~λ _{0} and center-to-center distance of 0.44~λ _{0} . Furthermore, the validation of extending to large-scale 1-D and 2-D arrays is also discussed. Featuring simple structure, compressed dimension, strong-coupling suppression, and good radiation performance, the proposed decoupling scheme possesses promising potential for antenna array applications.